Deciphering the human antibody response against Burkholderia pseudomallei during melioidosis using a comprehensive immunoproteome approach - Wagner, Gabriel E.; Stanjek, Thomas Franz Paul; Albrecht, Dirk; Lipp, Michaela; Dunachie, Susanna J.; Föderl-Höbenreich, Esther; Riedel, Katharina; Kohler, Anne; Steinmetz, Ivo; Kohler, Christian (Frontiers in Immunology, 2023)
The environmental bacterium Burkholderia pseudomallei causes the often fatal and massively underreported infectious disease melioidosis. Antigens inducing protective immunity in experimental models have recently been identified and serodiagnostic tools have been improved. However, further elucidation of the antigenic repertoire of B. pseudomallei during human infection for diagnostic and vaccine purposes is required. The adaptation of B. pseudomallei to very different habitats is reflected by a huge genome and a selective transcriptional response to a variety of conditions. We, therefore, hypothesized that exposure of B. pseudomallei to culture conditions mimicking habitats encountered in the human host might unravel novel antigens that are recognized by melioidosis patients. In this study, B. pseudomallei was exposed to various stress and growth conditions, including anaerobiosis, acid stress, oxidative stress, iron starvation and osmotic stress. Immunogenic proteins were identified by probing two-dimensional Western blots of B. pseudomallei intracellular and extracellular protein extracts with sera from melioidosis patients and controls and subsequent MALD-TOF MS. Among B. pseudomallei specific immunogenic signals, 90 % (55 out of 61) of extracellular immunogenic proteins were identified by acid, osmotic or oxidative stress. A total of 84 % (44/52) of intracellular antigens originated from the stationary growth phase, acidic, oxidative and anaerobic conditions. The majority of the extracellular and intracellular protein antigens were identified in only one of the various stress conditions. Sixty-three immunoreactive proteins and an additional 38 candidates from a literature screening were heterologously expressed and subjected to dot blot analysis using melioidosis sera and controls. Our experiments confirmed melioidosis-specific signals in 58 of our immunoproteome candidates. These include 15 antigens with average signal ratios (melioidosis:controls) greater than 10 and another 26 with average ratios greater than 5, including new promising serodiagnostic candidates with a very high signal-to-noise ratio. In conclusion, our study shows that a comprehensive B. pseudomallei immunoproteomics approach, using conditions which are likely to be encountered during infection, can identify novel antibody targets previously unrecognized in human melioidosis.